Inter-laboratory Comparison of the Measuring and Calculation Results of Electric Field Strength near 35 kV Overhead Power Lines - Grbić, Maja Đ; Pavlović, Aleksandar; Vulević, Branislav (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
The paper presents an inter-laboratory comparison of the measuring and calculation results of the electric field strength near 35 kV overhead power lines, in which three testing laboratories participated. This inter-laboratory comparison was undertaken for the purpose of ensuring confidence in the quality of the test results. Measuring and calculation results are analysed with standard methods, using Еn number, based on which the valuation of the laboratories was performed.